Analysis of the importance of public infrastructure policy for the execution of the Tunnel de la Línea work, in the period 2004-2020 (2020)
In this paper you will find an analysis of public policies in Colombia for the infrastructure sector of the last sixteen years, which allowed the development of the Central Cordillera Crossing Project, Tunnel of the Line. Starting from the importance of the economic and commercial progress of the country, from the transport sector that contributes competitiveness, the actions implemented by the governments during this period are analyzed to consolidate one of the most important road development works. A historical journey of the evolution of the work is presented, from its initial conception, going through the milestones of execution and contracting, until reaching the country's expectations with its commissioning. In addition, some assessments are made on the difficulties experienced and recommendations to improve for the future in the development of infrastructure works.